Legalising the drug wars: a regulatory history of UN drug control - Collins, John (Cambridge University Press, 2022)
Introduction -- Drug diplomacy from the opium wars through The League Of Nations, 1839-1939 -- International drug control in wartime , 1939-1945 -- Creating the UN Commission on Narcotic Drugs, 1945-1946 -- Reconstructing drug control in Europe, Asia and the Middle East -- Old battles a new at the UN Commission on Narcotic Drugs, 1946-1948 -- Dividing up the global licit market, 1948-1953 -- From the 1953 protocol to the 1961 single convention -- Assessing the legal legacy of the single convention -- Conclusion : UN drug control in the twenty-first century - towards a regime complex?